Cognitive impairments in schizophrenia and their impact on oxidative stress - A. S. Piatoikina; T. V. Zhilyaeva; G. E. Mazo (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2022)
The article is devoted to modern concepts of cognitive disorders in schizophrenia. Neurocognitive deficits can be expressed in impaired attention, auditory memory, motor skills, working memory, processing speed and executive function. The attention of researchers is currently being paid to the violation of the speed of information processing and character encoding that can lead to impaired social functioning in patients with schizophrenia. Two hypotheses about the dynamics of neurocognitive impairments in schizophrenia are also considered: the theory of «static encephalopathy» and progressive impairment of cognitive functions.This review evaluates the results of a comparative analysis of the effectiveness of first and second generation antipsychotics in the treatment of cognitive dysfunction. As a result of the analysis of the available data, it was concluded that first-generation antipsychotics most likely do not directly impair cognitive abilities, but they can do so indirectly, due to the simultaneous use of anticholinergic drugs that compromise some neurocognitive abilities. Second-generation antipsychotics have an advantage over first-generation drugs, however, it has been argued that most antipsychotics lead to a slight improvement in cognitive functioning, and there is no specific effect on its specific domains.An analysis of data on the relationship between oxidative stress markers and psychopathological characteristics and cognitive profile of patients with schizophrenia was carried out. In particular, the mechanism of stress-induced cell death in the prefrontal and anterior frontal regions and a decrease in brain volume in these regions, leading to a decrease in cognitive and executive functions, are considered. In addition, the mechanisms of association of redox imbalance with brain-derived neurotrophic factor (BDNF) depletion, hypofunction of the NMDA receptor, changes in the level of pro-inflammatory cytokines, neurogenesis, and cell apoptosis were considered.